2002
DOI: 10.1017/s0016756801006264
|View full text |Cite
|
Sign up to set email alerts
|

The break-up of East Gondwana along the northeast coast of Oman: evidence from the Batain basin

Abstract: Recent detailed studies on the Batain nappes (northeast coast of Oman), which represent a special part of the so-called ‘Oman Exotics’, have led to a better understanding of the Neotethyan geo-dynamic evolution. The Batain Exotics bear witness to volcanic activity, sea-level changes, tectonic instability, rifting and oceanization along the Eastern Oman margin during Late Palaeozoic and Mesozoic times. They allow definition of the Batain basin as an aborted Permian branch of Neotethys. This marine bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The breakup of Pangea began during the Norian in the Late Triassic, and included the opening of parts of the western Tethys (Hauser et al, 2002). However, in southern Europe, the first rifting phases started in the Early Triassic, and carbonate platforms developed in the Calcareous Alps and the Inner Carpathians (Ciarapica, 2007;Golonka, 2007;Golonka et al, 2018).…”
Section: Europementioning
confidence: 99%
“…The breakup of Pangea began during the Norian in the Late Triassic, and included the opening of parts of the western Tethys (Hauser et al, 2002). However, in southern Europe, the first rifting phases started in the Early Triassic, and carbonate platforms developed in the Calcareous Alps and the Inner Carpathians (Ciarapica, 2007;Golonka, 2007;Golonka et al, 2018).…”
Section: Europementioning
confidence: 99%
“…Their size varies from a metric to a kilometric scale. Palaeogeographically, the oceanic series of the Batain Plain were deposited in a distinct southern branch of the Neotethys that separated Arabia from India and Madagascar (Hauser et al 2002).…”
Section: Geological Contextmentioning
confidence: 99%
“…The Batain nappes of eastern Oman comprise Permian-to-Cretaceous volcanic rocks and sediments (Immenhauser et al, 2000). Permian carbonate blocks with a rich bryozoan assemblage belong to the Lower Triassic Aseelah Unit of the Saal Formation (Hauser et al, 2002;Weidlich, 2007). The age of the blocks is under discussion.…”
Section: Age Stratigraphy and Paleoecologymentioning
confidence: 99%
“…The age of the blocks is under discussion. The oldest blocks could have a Sakmarian-Artinskian (Shackleton et al, 1990;Immenhauser et al, 2000;Hauser et al, 2002) or late Artinskian-Kubergandian age (D. Vachard, personal, comm.). Many blocks are dated as Guadalupian, based on smaller foraminifers and fusulinids (Vachard et al, 2001(Vachard et al, , 2002; also, a Lopingian block has been found (L. Krystyn, pers.…”
Section: Age Stratigraphy and Paleoecologymentioning
confidence: 99%